Interorganizational network portfolios of nonprofit organizations: Implications for collaboration management - Fu, Jiawei Sophia; Cooper, Katherine R. (Nonprofit management & leadership, 2021)
Increasingly, nonprofit organizations engage in interorganizational collaboration to address large‐scale social problems. Scholarship typically focuses on the characteristics of both within‐sector and cross‐sector partnerships of two collaborating organizations or all partnering organizations involved in a collaboration, but we know little about the patterns of interorganizational relationships that single nonprofit organizations maintain. This research draws upon surveys from 452 nonprofits and introduces nonprofit network portfolios, which we define as the number, integration, intensity, and duration of relationships that nonprofits purposefully develop with other organizations. Using 12 network measures, Ward cluster analysis revealed three distinct network portfolios: restricted within‐sector (n = 319, 70.58%), which included limited collaboration and prioritized within‐sector partnerships; robust within‐sector (n = 80, 17.70%), which included more nonprofit partnerships than restricted within‐sector portfolios; and cross‐sector (n = 53, 11.72%), which had a rich assemblage of integrative partnerships with nonprofits, businesses, and government agencies. Further, nonprofits that maintained each type of portfolio differed in their revenue and social mission, suggesting these factors are related to the types of collaboration that nonprofits maintain. This study makes contributions to existing research on interorganizational networks and cross‐sector collaboration and suggests practical and policy implications for nonprofit network management.